The Tapai Festival as the Cultural Heritage of the Malay Community of Batu Bara: Historical Reconstruction and Analysis of Its Social Meaning - Farhana Aziz Batu Bara; Laila Rohani (Local History & Heritage, 2026)
This study examines the Tapai Festival as a cultural heritage of the Malay community in Batu Bara Regency by focusing on its historical reconstruction and symbolic social meaning within a changing socio-cultural context. This study uses a qualitative method with a historical approach and field studies. Data were obtained through observation, interviews, and literature studies related to Malay traditions and culture. The findings reveal that the Tapai Festival operates as a symbolic cultural system in which food practices function as a medium of social negotiation, reinforcing kinship-based reciprocity and collective memory rather than merely strengthening community solidarity. This tradition reflects structured patterns of togetherness and mutual cooperation that institutionalize intergenerational transmission of cultural knowledge through ritualized practices. The study argues that the Tapai Festival constitutes an intangible cultural heritage that sustains Malay cultural identity in Batu Bara while offering a conceptual contribution to understanding how local traditions function as adaptive cultural mechanisms in response to modern social transformations.